Molecular detection of Mycobacterium tuberculosis sensitivity to rifampicin and isoniazid in South Gondar Zone, northwest Ethiopia - Alelign, Amir (BMC Infect Dis, 2019)
BACKGROUND: Drug resistant tuberculosis (TB) has become a persistent health threat in Ethiopia. In this respect, baseline data are scarce in many parts of high TB burden regions including the different zones of Ethiopia. METHODS: A total of 111 culture positive M. tuberculosis isolates were recovered from TB patients and identified using region of difference (RD) 9 based polymerase chain reaction (PCR) and spoligotyping. Thereafter, their drug sensitivities to Rifampicin (RIF) and Isoniazid (INH) were evaluated using GenoType MTBDRplus assay. RESULTS: The result showed that 18.0% (20/111) of the isolates were resistant to either RIF or INH. Furthermore, 16.7 and 23.8% of the isolates from new and retreatment cases were resistant to any of the two anti-TB drugs, respectively. Multi-drug resistant (MDR) TB was detected on 1.8% (2/111) of all cases. Significantly higher frequencies of any drug resistance were observed among Euro-American (EA) major lineage (χ(2): 9.67; p = 0.046). CONCLUSION: Considerably high proportion of drug resistant M. tuberculosis strains was detected which could suggest a need for an increased effort to strengthen TB control program in the study area.